Dissemination of Carbapenemases (KPC, NDM, OXA-48, IMP, and VIM) Among Carbapenem-Resistant Enterobacteriaceae Isolated From Adult and Children Patients in China - Han, Renru; Shi, Qingyu; Wu, Shi; Yin, Dandan; Peng, Mingjia; Dong, Dong; Zheng, Yonggui; Guo, Yan; Zhang, Rong; Hu, Fupin; , China Antimicrobial Surveillance Network (CHINET) Study Group (Frontiers in Cellular and Infection Microbiology, 2020)
This study aimed to investigate the dissemination and characteristics of blaKPC, blaNDM, blaOXA-48-like, blaIMP, and blaVIM among the carbapenem-resistant Enterobacteriaceae (CRE) strains isolated from adult and children patients. A total of 935 non-duplicate CRE strains were collected from 36 hospitals in 24 provinces or cities across China from 2016 to 2018. Antimicrobial susceptibility testing was performed by broth microdilution method and carbapenemase genes blaKPC, blaNDM, blaOXA-48-like, blaIMP, and blaVIM were screened by PCR and confirmed by DNA sequencing. Overall, carbapenemases were produced in 97.4% (911/935) of CRE strains, including KPC-2 (51.6%, 482/935), NDM (35.7%, 334/935), and OXA-48-like carbapenemases (7.3%, 68/935). Overall, the most prevalent carbapenemase gene was blaKPC-2 among Klebsiella pneumoniae (64.6%, 457/709) and the CRE strains isolated from adult patients (70.3%, 307/437), and blaNDM among Escherichia coli (96.0%, 143/149) and the CRE strains from children (49.0%, 247/498). The blaOXA-232-positive carbapenem-resistant K. pneumoniae (9.3%, 66/709) were all isolated from children. Sixteen strains were positive for blaIMP and 9 strains produced multiple carbapenemases. No strain was positive for blaVIM. Most of the CRE strains (>90%) were resistant to cephalosporins and carbapenems, more than half (>50%) were resistant to aminoglycosides and fluoroquinolones, but the majority (95.8 and 98.4%) were susceptible to polymyxin B and tigecycline. Ceftazidime-avibactam showed excellent in vitro activity against blaKPC-2 and blaOXA-48-like positive strains (100% susceptible). In China, KPC-2, NDM, and OXA-48-like carbapenemases were predominant among CRE clinical isolates. The most prevalent carbapenemase gene was blaKPC-2 among K. pneumoniae isolates from adult patients, and blaNDM among E. coli isolates from children.